Young Women’s Experience of Sexuality: A Battle of Pleasure and Sexual Purity in the Context of Malaysian Society - Fazli Khalaf, Zahra; Liow, Jun Wei; Low, Wah Yun; Ghorbani, Behzad; Merghati-Khoei, Effat (Springer, 2018)
Little is known regarding the ways in which Malaysian women’s sexuality is constructed, and how their personal experiences, culture, religion and society influence their feeling, attitude and sexual behaviours. This study explored the sexual experiences of young adult women in the developing context of the country. A qualitative phenomenological approach was adopted. Purposive sampling was employed, and a total of 20 participants were recruited, comprised of the major ethnic groups in Malaysia. Four main themes emerged through the phenomenological analysis of the data, including: conditional pleasure; social honour and women’s purity; risk and responsibility; and transcendence of love and emotion. The findings of this study revealed that sexuality was experienced under the control of religion and society with the concern of conserving a woman’s purity and social honour; and imposing risks and responsibility on women. Despite the awareness of women’s right to experience sexual pleasure, it was commonly perceived that sexual activities beyond the social norms will result in social shaming and guilt. The authors recommend appropriate sexuality education regarding sexual assertiveness and communication, safe-sex practices, and improving sexual decision-making skills.